Determinan Keberhasilan UMKM Berbasis Ekonomi Kreatif di Kabupaten Bantul - Sri Widodo; Afri Ovita (Universitas PGRI Madiun, 2021)
Micro, small and medium enterprises are one of the economic sectors that have a significant role in the country's economy, and Indonesia is no exception. In Indonesia, MSMEs have a role in increasing the country's Gross Domestic Product (GDP) and absorbing labor which can reduce unemployment. The purpose of this study was to determine the effect of using accounting information, business capital, and business age on the success of creative economy-based SMEs in Bantul Regency. The sample in this study was selected by purposive sampling, as many as 197 respondents. The analysis technique used in this study uses multiple linear regression analysis. The results of the study prove that the use of accounting information and business age have an effect on business success, while business capital has no effect on business success. The implications of this research are for MSMEs to increase the use of accounting information and maximize the use of business capital